2021
DOI: 10.1108/jedt-09-2020-0354
|View full text |Cite
|
Sign up to set email alerts
|

Potential of adopting a resilient safety culture toward improving the safety performance of construction organizations in Nigeria

Abstract: Purpose Despite the efforts of organizations to improve safety performance, shortfalls of the strategies have been reported in numerous studies around the globe. However, previous studies in countries with more organized construction sectors show that adopting a resilient safety culture by organizations has a tendency of improving safety performance. As safety culture is dynamic which differs with geographical context, the purpose of this paper is to achieve two objectives: testing the causal relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Sensor-based safety technologies also have great potentials in identifying and eliminating preventable safety hazards rooted in the design phase before construction commencement (Asadzadeh et al , 2020). Most notably, to curb accidents in the industry, it is necessary that all potential hazards are discovered in the early design and planning phases and corrective measures are taken (Abubakar et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Sensor-based safety technologies also have great potentials in identifying and eliminating preventable safety hazards rooted in the design phase before construction commencement (Asadzadeh et al , 2020). Most notably, to curb accidents in the industry, it is necessary that all potential hazards are discovered in the early design and planning phases and corrective measures are taken (Abubakar et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A safety climate can be presumed as a realistic and surface-level reflection of the organization’s safety culture (Flin et al , 2000), which summarizes the employees’ views and attitudes toward their safety (Griffin and Curcuruto, 2016). Moreover, Clarke (2006), Neal and Griffin (2006), Chen et al (2017) and Abubakar et al (2021) among others, have identified a safety climate as a significant factor that influences safety behavior. The findings show that this hypothesis is correct and supported and that the safety environment at an NPP creates positive safety behaviors by increasing safety compliance and participation.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between safety climate and safety behavior. Safety climate can be described as a combination of attitudes and values of employees, individually and in a team, which can be represented as a commitment toward the management of safety in an organization (Wilpert and Itoigawa, 2003;Abubakar et al, 2021). The first studies to provide a correlation between safety climate and behavior were by Griffin and Neal (2000) and Neal and Griffin (2006).…”
Section: Relationship Between Empowering Leadership and Safety Behaviorsmentioning
confidence: 99%
“…In their work, Abubakar et al (2022) emphasise the crucial role that organisational culture and leadership play in determining the health and safety procedures used on Nigerian construction sites. In order to create a positive safety atmosphere, their findings highlight the importance of strong leadership commitment, a supportive organisational culture and effective communication.…”
Section: Literature Review 21 Health and Safety Practices In Construc...mentioning
confidence: 99%
“…In their work, Abubakar et al . (2022) emphasise the crucial role that organisational culture and leadership play in determining the health and safety procedures used on Nigerian construction sites.…”
Section: Literature Reviewmentioning
confidence: 99%